Reconstructing The Relationship Regional Representative Council of The Republic of Indonesia with Regional Government for The Optimization of Regional Autonomy - Ryantoni, Hanugra; Pieris, John; Siahaan, Maruarar; Narang, Agustin Teras (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
As a regional representative institution, the Regional Representative Council of The Republic of Indonesia (DPD) was born from the idea of changing the representative system into a two-chamber representative system and increasing regional participation in the course of politics and state management. The ideal concept of DPD, was initially to accommodate the principle of regional representation and regional empowerment. DPD as a regional representative in carrying out its duties and functions requires effective coordination with the Regional Government as the executor of executive power in the region. Empirically, the construction of the relationship between the DPD and the regional government is currently not optimal. One of the obligations of the DPD is to follow up on regional aspirations and interests is still carried out normatively and ineffectively. This is certainly not ideal as the construction of Article 18, Article 18A, Article 18B, Article 22D, and Article 23 of the UUD 1945 are interrelated. Where the presence of the DPD (in Article 22D) as a regional representative institution is necessary to maintain the existence of the region (Article 18, Article 18A, and Article 18B). Based on the research findings, it is important to recommend that central government along with the DPR and DPD need to consider special arrangements in the form of affirmation of decentralized authority and effective central-regional relations, especially to resolve regional problems. Meanwhile, there needs to be a reconstruction of the DPD's supervisory and budget functions that have a direct impact on the community and regions; optimization of existing functions, such as the monitoring and evaluation function of draft regional regulations and regional regulations, as well as the monitoring and review function of laws for the harmonization of central-regional laws; and there needs to be a pattern of support for the DPD to optimize its performance.